Web-Based RESTful Monitoring of Water Level and Nutrient Concentration In Hydroponic Systems - Rahmat Fadli Isnanto; M. Dzaki Akhyar; Sutarno; Sarmayanta Sembiring (Universitas Medan Area, 2026)
Hydroponics requires continuous monitoring of water level and nutrient concentration. This study implements a web-based monitoring system with ESP32, TDS sensor, and water level sensor. Sensor data is sent via RESTful API to a Laravel server and displayed on a responsive dashboard. The main scientific contribution is the implementation of a decoupled RESTful API middleware between hardware and presentation layers, differing from platform-centric approaches. Analysis of 41 sensor readings revealed two operational clusters. The first cluster (20 samples) showed an average of 279.5 ppm (CV 15.2%) with constant water level at 4.8 cm. The second cluster (21 samples) showed an average of 3450.2 ppm (CV 3.5%) with water level at 6.4 cm. Two outliers (3963 ppm and 3751.6 ppm) were identified in the high-concentration cluster, likely due to transient mixing. No significant temporal trends were observed within clusters. API testing achieved 100% success rate, latency <750 ms, and theoretically supports throughput of 185 requests/second with horizontal scalability. A traceability matrix confirmed all six functional requirements. The decoupled RESTful middleware overcomes IoT platform interoperability limitations, enabling future expansion and supporting real-time hydroponic monitoring for urban agriculture